V. 5, N. (1), Jan./Abri. 2020 - Correia, Divanise Suruagy (Revista Portal: Saúde e Sociedade, 2020)
AVALIADORES DO V.5, N. 1, JAN./ABR. 2020 Michel Machado Andrea Ferreira Carlos Souza Divanise Correia Mércia Medeiros Maria Taveira Sandra Lopes Francisco Passos Rozangela Wyszomirska Editoração Eletrônica Divanise Suruagy Correia Paulo Rozendo da Paixão Capa